Systematic Review of Pre-injury Migraines as a Vulnerability Factor for Worse Outcome Following Sport-Related Concussion - Terry, Douglas P.; Büttner, Fionn; Huebschmann, Nathan A.; Gardner, Andrew J.; Cook, Nathan E.; Iverson, Grant L. (Frontiers in Neurology, 2022)
Background Individuals with migraine disorders may be affected differently by concussions compared to individuals without migraine disorders. Prior studies on this topic have had mixed results. The purpose of this study was to systematically examine clinical outcomes following a sport-related concussion in athletes who have a pre-injury history of migraines. Methods All studies published prior to 15 May 2021 that examined pre-injury migraines as a possible predictor of clinical recovery from concussion were included. The search included (i) sport/athlete-related terms, (ii) concussion-related terms, and (iii) diverse predictor/modifier terms. After removing duplicates, 5,118 abstracts were screened, 538 full-text articles were reviewed, and 27 articles were included for narrative synthesis without meta-analysis (n = 25 with unique samples). Risk of bias was assessed using the domain-based Quality In Prognosis Studies (QUIPS) tool. Results Most studies did not find pre-injury migraines to be associated with concussion outcome, but several of these studies had small or very small sample sizes, as well as other methodological weaknesses. Risk of bias varied greatly across studies. Some of the larger, better-designed studies suggested pre-injury migraines may be a risk factor for worse concussion outcome. Most articles examined pre-injury migraines as an exploratory/secondary predictor of concussion outcome; very few were designed to examine migraine as the primary focus of the study. Migraine history was predominantly based on self-report and studies included minimal information about migraine (e.g., age of onset, frequency/severity, past treatment). Effect sizes were usually not reported or able to be calculated from reported study data. Conclusion There is some evidence to suggest that pre-injury migraines may be a vulnerability factor for a worse outcome following concussion, with studies having the lowest risk of bias reporting a positive association. Future studies should focus on improving methodological quality when assessing the relationship between pre-injury migraines and concussion outcome and better characterizing pre-injury migraine status. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42019128292, identifier: PROSPERO 2019 CRD42019128292.